Determinants of side selling behaviour in emerging sorghum supply chains in Kisumu County, Kenya - Janet Sigara Nyamamba; Oscar Ingasia Ayuya; Kenneth Waluse Sibiko (Cogent Economics & Finance, 2022)
Vertical coordination in agriculture has received popularity in recent years. They have emerged to transform farm enterprises from subsistence farming to commercially oriented production. Despite the importance attached to them, some farm enterprise owners are involved in side selling even though they are committed to specific vertical coordination strategic options. Factors influencing this behaviour are still unclear in the empirical literature. This study intends to bridge this gap by determining the extent of side selling in sorghum supply chains in Kisumu County. A stratified sampling technique was used to collect data from 266 sorghum farm enterprises. Primary data was obtained through interviews using a pre-tested semi-structured questionnaire administered by trained enumerators. The study used Fractional Response Model to determine the extent of side selling among sorghum farm enterprises. Results from Fractional Response Model reveal that farming experience, better prices from alternative markets, neighbourhood effect, frequency of contacts, low bargaining power and network externalities influence side selling positively. Whereas other forms of income, land size, credit access and trust reduces the probability of side selling. These results indicate that policymakers should generate policies that will strengthen the legal institutions in agriculture regarding breaching of agreements reducing the side selling behaviours of sorghum producers.
Keywords: 330; side selling; supply chain; vertical coordination strategic options; verticalcoordination